Exposing Narrative Exposure Therapy: investigating autobiographical memory integration and the process of exposure and habituation in Narrative Exposure Therapy - Lord, Jackson; Schroder, Thomas; Sabin-Farrell, Rachel; Naidoo, Rohan (2023)
Introduction: Witnessing or being involved in traumas can lead to the development of post-traumatic stress disorder (PTSD). If people are subjected to multiple prolonged traumas this can lead to complex PTSD (CPTSD). Narrative Exposure Therapy (NET) is a treatment used for CPTSD; however, its autobiographical memory integration (ABMI) and exposure and habituation mechanisms of change are not well evidenced. The role of autobiographical memory (ABM) in therapeutic change needs to be explored. It is not appropriate to apply the existing measures of ABM to trauma narratives gained from therapy; therefore, the researcher developed the autobiographical memory integration coding tool (ABMICT). The NET protocol was adapted (termed NET+; Table 2) to allow its mechanisms of change to be examined.